Descending Viewer Method for Fault Tolerant Control - K. Lenin (Institute of Advanced Engineering and Science, 2018)
In this paper Descending Viewer Method (DVM) projected for finding and fault tolerant control of stator inter-turn short circuit faults in doubly-fed induction generators based in wind turbine. A process has been developed that allows the way from ostensible controllers designed for strong condition, to vigorous controllers designed for defective condition. Finally value of the rotor resistance estimated & is based on the use of the error between real and probable value of doubly fed induction generator (DFIG) in faulty condition, this will perk up the performance of this viewer. Simulation results show the reliability of the proposed Descending Viewer Method (DVM) approach.